Column liquid chromatography-ultraviolet and column liquid chromatography/mass spectrometry evaluation of stress degradation behavior of escitalopram oxalate - Dhaneshwar, Sunil R.; Mahadik, Mahadeo V.; Kulkarni, Mahesh J. (Journal of AOAC international, 2009)
{The objective of this work was to study the degradation behavior of escitalopram oxalate under different International Conference on Harmonization (ICH)-recommended stress conditions by column liquid chromatography (LC)-UV and LC/mass spectrometry (LC/MS) and to establish a validated stability-indicating LC assay method. Escitalopram oxalate was subjected to stress conditions of hydrolysis, oxidation, photolysis, and thermal decomposition. Extensive degradation was found to occur in alkaline medium. Mild degradation was observed in acidic and oxidative conditions. Escitalopram oxalate was stable to neutral, photolytic, and thermal stress. Successful separation of the drug from degradation products formed under stress conditions was achieved on a PerfectSil-100 ODS-3 column [C(18) (5 mu m, 25 cm x 4.6 mm id)] using methanol-0.01 M acetate buffer pH 3.8 adjusted with acetic acid (45 + 55) as the mobile phase. The flow rate was 1 mL/min, and the detection wavelength was 239 nm. The method was validated according to ICH guidelines. Major degradation products formed in hydrolysis and oxidative conditions were isolated, and structural elucidation of degradation products was done by LC/MS and infrared spectrometry studies. The major hydrolysis degradation product was confirmed as 1-(3-dimethylaminopropyl)-1-(4-fluoro-phenyl)-1,3dihydroisobenzofuran-5- carboxylic acid, and the major oxidative degradation product was confirmed as 1-{[3-dimethylamino(oxide)-propyl]-1(4-flurophenyl)}-1,3-dihydro-iso benzofuran-5-carbonitrile.